Initiative for Minimum Salary Regulation of the European Union - Opportunities and Challenges - Moraliyska–Ivanova, Monika (Research Papers, 2022)
The purpose of this article is to examine the issue connected with the European proposal to regulate minimum wages in the EU. In October 2020, the European Commission presented a draft directive on the EU minimum wage, which aims to ensure decent wages for workers. The article’s tasks are to assess the current situation with the minimum wage in the EU, the expected effects of the directive and the main challenges related to its implementation. The methodology includes comparative analysis, statistical analysis, induction and deduction. The main results include an analysis of the proposal for regulation, presentation of different approaches for defining the minimum wage, and forecasts for the effect of its implementation.
Keywords: Regulation; Directive; Minimum wage; Social europe; European union